The Representation of Sufism Moral Values in The Book Kiai Nyentrik Membela Pemerintah Oleh Abdurrahman Wahid - Mukhlas Habibi; Lailatul Hidayati (Universitas Sebelas Maret, 2024)
This research discusses the moral degradation that occurs in modern society. Moral degradation can be seen through various aspects, such as a decrease in ethical values, an increase in individualistic behavior and the misuse of information and communication technology. Many people are more concerned with personal interests than social interests, resulting in a lack of empathy and solidarity. This reality can be overcome with Sufism morality. By implementing the moral values of Sufism, it will make human beings as a person who is refined in soul and polite in their ethics so that they can develop self-awareness and return to noble values so that a more civilized and harmonious social order is created. The purpose of this research is to represent the moral values of Sufism in the book Kiai Nyentrik Membela Pemerintah by K.H Abduraahman Wahid. This study uses a descriptive qualitative form with the type of library research and uses content analysis techniques as a form of data analysis. In the book Kiai Nyentrik Membela Pemerintah by K.H Abdurrahman Wahid, there are moral values of Sufism that are explained through the behavior of the characters who are the kiai contained in the book. The moral values of Sufism depicted in the book are sincerity, patience, gratitude, tawakkal, compassion, and humility. The book Kiai Nyentrik Membela Pemerintah is a collection of essays written by K.H Abdurrahman Wahid and then published by LkiS Yogyakarta. In the book, there is an overview of the behavior of the kiai who implement the moral values of Sufism in their daily lives that can be emulated by today's society